Growing up in Nature: Health and Adolescent Dance in L.M. Montgomery’s Emily Series - Macquarrie, Jenn (Studies in Canadian Literature, 2011)
As the 1890s closed, a new vision of dance was being formed in North America; modern dance, as envisioned by iconic dancer Isadora Duncan, would create a nation of healthy, strong bodies. The same vision of a creative, empowering nature, articulated through the contemporary language of dance and movement, permeates L.M. Montgomery’s Emily series. Ideas about the freedom of dance and the inspirational power of nature, as outlined by Duncan and by Francis Delsarte, are integral to the construction of adolescent health in Montgomery’s texts. Like Duncan and Delsarte, Emily Starr understands the link between her interior soul and external nature, and seems unable to resist expressing that connection through movement. Furthermore, Emily displays what Duncan describes as the natural desire for freedom of all living things. She proves that dancing can be beneficial mentally, physically, and morally, and shows that movement – particularly in nature – can free the adolescent soul.